Experimental observations and dynamic modeling of vibration characteristics of a cylindrical roller bearing with roller defects. (April 2020) - Niu, Linkai; Cao, Hongrui; Hou, Huipeng; Wu, Bing; Lan, Yuan; Xiong, Xiaoyan
Highlights: A dynamic model is proposed for cylindrical roller bearings with roller defect. Vibration responses as a roller defect rolls around a race are studied. The multiple-impulse phenomenon is investigated. Observation of experiment results of the vibration is reported. Abstract: The better understanding of the vibration characteristics of a bearing with defects is crucial for the fault diagnosis of rolling element bearings (REBs). In the current paper, the vibration responses of a cylindrical roller bearing when a roller defect goes around outer and inner races are investigated. Firstly, an experiment was carried out and the experimental results are observed to discuss the multiple impulses which are generated when a roller defect goes around a race. Then a dynamic model is proposed for cylindrical roller bearings with roller defects. In the proposed dynamic model, the relative slippage, the finite size of a roller, and the change of contact force direction as a roller defect impacts with a race are all considered. Based on the proposed dynamic model, the vibration responses of the bearing when a roller defect goes around the outer and the inner races are investigated. The results show that, besides the impulses generated when the roller edges roll through the line connecting the roller and race centers, other impulses can also be generated due to the impact between the roller defect and the race. Furthermore, the roller defect impacts both with the outer race and the inner race as it rotates in the loaded zone, while the roller defect only impacts with the outer race in the unloaded zone for the radially loaded cylindrical roller bearing. In addition, the interaction time between the roller defect and the inner race is generally longer than that between the roller defect and the outer race.